2016
DOI: 10.2135/cropsci2013.11.0737er
|View full text |Cite|
|
Sign up to set email alerts
|

Defining Sufficiency Levels of Nitrogen in Cool‐Season Turfgrass Lawns Using Macy's Concept

Abstract: Few correlation or calibration studies have been conducted to determine or validate sufficiency levels of N concentrations in the clippings of turfgrass for color and growth responses. In a series of field experiments conducted across six consecutive growing seasons (2007–2012) in Connecticut, clipping samples of Kentucky bluegrass (Poa pratensis L.) and tall fescue (Festuca arundinacea Schreb.) lawns were used to estimate yields and then analyzed for N concentrations. Chlorophyll and normalized difference veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The most common spectral reflectance measurement for turfgrass is NDVI. Measurements of NDVI have been used to objectively assess turfgrass response in relation to N rates, soil N concentrations, or tissue N concentrations (Trenholm et al, 2001; Bell et al, 2002, 2004; Fitz‐Rodríguez and Choi, 2002; Stiegler et al, 2005; Trenholm and Unruh, 2005; Kruse et al, 2006; Baghzouz et al, 2007; Xiong et al, 2007; Barry et al, 2009; Johnsen et al, 2009; Flowers et al, 2010; Li et al, 2011; Zhu et al, 2012; Agati et al, 2013; Geng et al, 2014a, 2014b).…”
Section: Methodsmentioning
confidence: 99%
“…The most common spectral reflectance measurement for turfgrass is NDVI. Measurements of NDVI have been used to objectively assess turfgrass response in relation to N rates, soil N concentrations, or tissue N concentrations (Trenholm et al, 2001; Bell et al, 2002, 2004; Fitz‐Rodríguez and Choi, 2002; Stiegler et al, 2005; Trenholm and Unruh, 2005; Kruse et al, 2006; Baghzouz et al, 2007; Xiong et al, 2007; Barry et al, 2009; Johnsen et al, 2009; Flowers et al, 2010; Li et al, 2011; Zhu et al, 2012; Agati et al, 2013; Geng et al, 2014a, 2014b).…”
Section: Methodsmentioning
confidence: 99%
“…Dumort. ], 33–51 g kg −1 for perennial ryegrass, and 25–51 g kg −1 for Kentucky bluegrass (Mills & Jones, 1996), 27–35 g kg −1 for various species (Turner & Hummel, 1992), 30.4 to ≥34.7 g kg −1 for Kentucky bluegrass (Badra et al., 2006), 30–34 g N kg −1 for mixed species and separately for Kentucky bluegrass (Mangiafico & Guillard, 2007), and 32–46 g kg −1 and 28–42 g kg −1 for Kentucky bluegrass and tall fescue, respectively (Geng et al., 2014). These previous studies, however, report total N concentrations in the clippings and not the verdure.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in verdure dry‐tissue extractable NO 3 –N concentrations when total N concentrations are >34 g kg −1 during the fall months (Figure 3) also suggests luxury consumption of N. This increase can be attributed to storage of NO 3 beyond that needed for maintenance as turfgrass plants were preparing for winter dormancy. Averaged across years and seasons, Kentucky bluegrass and tall fescue lawns exhibited luxury consumption of N when clippings N concentrations exceeded 42 and 46 g kg −1 , respectively (Geng et al., 2014). As a percentage of the maximum or plateau values, the estimated verdure total N concentrations ranged from 60 to 70% for the 24.5 kg N ha −1 rate, 68 to 81% for the 49 kg N ha −1 rate, and 81 to 100% for the 98 kg N ha −1 rate (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…A critical percentage exists between luxury consumption and poverty adjustment, and this approach has been used in turfgrass systems. Geng et al (2014) investigated Macy's concept using cool‐season turfgrasses and reported N sufficiency ranges were between 32 and 46 g kg ‐1 for Kentucky bluegrass ( Poa pratensis L.), whereas tall fescue ( Festuca arundinacea Schreb.) was slightly lower, with a range of 28 to 42 g kg ‐1 .…”
Section: Current Interpretationsmentioning
confidence: 99%
“…was slightly lower, with a range of 28 to 42 g kg ‐1 . Furthermore, Geng et al (2014) determined luxury consumption of N to be 46 and 42 g kg ‐1 in Kentucky bluegrass and tall fescue, respectively.…”
Section: Current Interpretationsmentioning
confidence: 99%